The Role of Innovative Web Tools for ESL Online Teaching amidst the Pandemic: A Disruptive Path for Continuity - Kingston, Carol Linda (8ISC Abstract Proceedings; 8ISC Abstract Proceedings, 2022)
Effective pedagogical online teaching practices can provide students the support in learning the language amidst the pandemic. Currently, bridging the gap between online teaching practices and learning continuity has been a compelling and strenuous task. How do the language teachers go about closing the gap? The call for integrating the online pedagogical instructional practices of the language to second language learners is of great magnitude. Implementing a challenging curriculum, designing standard academic content with the accessibility of materials for learning, offering relevant instruction with specific learning strategies for ESL learners is an educational crisis (UNESCO Learning Portal, 2020). When disasters and crises (man-made and natural) occur, institutions need to be resilient and find new ways to continue the teaching-learning tasks (Chang-Richards et al., 2013). Teaching is the key area; however, the pulse of curricula is felt, the methods of teaching, motivation, and participation of the learners as well. Self- Determination Theory (Ryan & Deci, 2000) contributes to learning the language. Teaching the breadth and depth of vocabulary, building reading comprehension and writing skills with certain strategies, and providing language use models and integration of all the skills can aid in the teaching and learning of the targeted language (Cobb, 2004 & Cohen, 2010; Freeman& Freeman, 2009; Sherris, 2008) This theoretical paper explores the advantages and disadvantages of pedagogical online teaching practices of teachers. Besides, it explores the flexible online modality that recalibrates the curriculum and implements a strategic plan for adoption and adaptation. Keywords : Pedagogical Practices, Second Language Learners, Learning Strategies, Empowering Learners, Action Plan